The Effect of Compensation and Work Environment Mediated by Organizational Culture on Lecturer Performance - Nika Arundina Lusty; Eny Ariyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of compensation and work environment on the performance of lecturers at Mercu Buana University by organizational culture as a mediating variable. The research method used is quantitative method. The object of this research is a lecturer at the Faculty of Economics and Business with the permanent lecturer category A with a sample of 92 people. Analysis and testing techniques use the Structural Equation Model–Partial Least Square (SEM–PLS). The test results show that compensation and work environment have a positive and significant effect on lecturer performance by organizational culture as mediating variable. Organizational culture fully mediates compensation, and the work environment on lecturer performance.